Incorporating local environmental factors into railway bridge asset management - Yianni, Panayioti C.; Neves, Luís C.; Rama, Dovile; Andrews, John D.; Dean, Robert (Elsevier, 2016)
A novel approach to comparing bridge deterioration rates under different environmental conditions is employed using a network analysis approach. This approach uses a matrix condition scoring system utilised by Network Rail (NR). It does not require any conversion factors which can introduce subjectivity. A number of different factors were analysed to ascertain if they have an effect on bridge deterioration. The key factors were identified and their deterioration profiles incorporated into a probabilistic Petri-Net (PN) model, calibrated with historical data. From these, comparative model outputs pinpointing which factors affect bridge deterioration the most can be computed. Finally, simulations were carried out on the PN model to evaluate which of the factors would have the most financial effect for a transport agency. This allows a bridge manager to categorise bridges in different deterioration sets allowing the definition of different optimal inspection and maintenance strategies for each set.